2013
DOI: 10.1111/vru.12089
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Computed Tomographic Subchondral Bone Lesions in the Scapulohumeral Joint of 32 Immature Dogs With Thoracic Limb Lameness

Abstract: Osteochondrosis is a common developmental abnormality affecting the subchondral bone of immature, large breed dogs. The purpose of this retrospective study was to describe CT lesions detected in scapulohumeral joints of 32 immature dogs undergoing CT for thoracic limb lameness. Eight dogs (14 scapulohumeral joints) had arthroscopy following imaging. Thirteen dogs (19 scapulohumeral joints) were found to have CT lesions, including 10 dogs (16 scapulohumeral joints) with subchondral bone lesions and 3 dogs with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Out of 13 arthroscopically confirmed lesions, CT and computed tomography arthrography failed to detect two subchondral bone lesions identified by arthroscopy, however detected three other subchondral bone lesions, which were not identified by arthroscopy. A previous study found that arthroscopy identified only 64% of osteochondral lesions identified on CT examination of canine scapulohumeral joints . Arthroscopic evaluation is limited to surface defects and may fail to detect lesions in deeper structures .…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Out of 13 arthroscopically confirmed lesions, CT and computed tomography arthrography failed to detect two subchondral bone lesions identified by arthroscopy, however detected three other subchondral bone lesions, which were not identified by arthroscopy. A previous study found that arthroscopy identified only 64% of osteochondral lesions identified on CT examination of canine scapulohumeral joints . Arthroscopic evaluation is limited to surface defects and may fail to detect lesions in deeper structures .…”
Section: Discussionmentioning
confidence: 78%
“…Although used as the reference standard for the purposes of this study, arthroscopy has been shown to miss valid lesions that are identified by CT, particularly those located in the joint periphery or deep to the synovial lining . In the current study, only intraarticular structures were assessed in order to minimize this bias.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, besides accurate assessment of site and extent of the lesion, cartilage, and subchondral bone changes, the detection of mineralized and non-mineralized loose bodies and the assessment of the biceps tendon and tendon sheath are mandatory for a detailed diagnosis, accurate prognosis, and adequate treatment. The use of more sensitive imaging modalities such as computed tomography (CT; [5,[11][12][13]), ultrasonography (US; [8,[14][15][16], and arthroscopy [17,18] aid in complete evaluation of the shoulder joint and should be discussed below. This case report describes the presence of a migrated osteochondral fragment in the biceps tendon sheath as a sequela to osteochondrosis dissecans of the caudal humeral head in a medium-sized dog.…”
Section: Introductionmentioning
confidence: 99%